Hidden gems: Scattered knowledge hampered freshwater jellyfish research over the past one‐and‐a‐half centuries - Florian Lüskow; Nicholas Bezio; Luciano Caputo; Xupeng Chi; Henri J. Dumont; Krishan D. Karunarathne; Pablo J. López‐González; Maciej K. Mańko; Guillaume Marchessaux; Kentaro S. Suzuki; Evgeny A. Pakhomov (Ecology and Evolution)
Abstract Freshwater jellyfish (= limnic medusa‐budding hydrozoans, FWJ) are a small group of cnidarians found on all continents except Antarctica in temperate to tropical latitudes. Members of this group belong primarily to three genera: Astrohydra, Craspedacusta, and Limnocnida. While Astrohydra and Limnocnida are typically restricted to the islands of Japan, Africa, and the Indian subcontinent, one species or potential species complex, Craspedacusta sowerbii, became globally invasive. Despite research going back about one‐and‐a‐half centuries, little is known about their phylogeny and ecology compared to marine jellyfish. Recent species distribution modelling, however, showed that by 2050, C. sowerbii will potentially extend their distribution ranges due to global warming to high‐latitude ecosystems and be present (medusa stage) for an extended time in the seasonal limnic production cycle. An increase in their relative ecological importance with temporal and spatial spreading is hypothesised. Only recently, it has been shown that the trophic roles of polyps and medusae and their prey overlap with other ecosystem members. In addition, medusa behaviour may cause trophic cascades and alter vertical nutrient distributions. However, polyps and other benthic life cycle stages are understudied. In globally, changing freshwater ecosystems that may become more accommodating for FWJ, an improved understanding of their population biology and ecosystem ecology is urgently needed. In this integrative review, we, therefore, explore reasons for the hampered historical research progress, contrast developments with those of marine cnidarians, compile and publish alongside an extensive and unprecedented literature database, and formulate avenues for future directions in FWJ research.